Analysis of human leukocyte antigen associations in human papillomavirus–positive and –negative head and neck cancer: Comparison with cervical cancer. Issue 10 (17th February 2022) - Ekanayake Weeramange, Chameera; Shu, Danhua; Tang, Kai Dun; Batra, Jyotsna; Ladwa, Rahul; Kenny, Lizbeth; Vasani, Sarju; Frazer, Ian H.; Dolcetti, Riccardo; Ellis, Jonathan J.; Sturm, Richard A.; Leo, Paul; et al.
Abstract : Background: Although the majority of human papillomavirus (HPV) infections are cleared by the immune system, a small percentage of them progress to develop HPV‐driven cancers. Cervical cancer studies highlight that HPV persistence and cancer risk are associated with genetic factors, especially at the human leukocyte antigen (HLA) genes. This study was conducted to investigate such associations in head and neck cancer (HNC). Methods: In all, 192 patients with HNC and 384 controls were genotyped with the Infinium Global Screening Array (Illumina, Inc). HLA variants were imputed with SNP2HLA, and an association analysis was performed by logistic regression. Results: HPV‐positive HNCs were significantly associated with single‐nucleotide polymorphisms (SNPs) at DRB1_32660090 ( P = 1.728 × 10 –6 ) and DRB1_32660116 ( P = 1.728 × 10 –6 ) and with the amino acid variant DRB1_11_32660115 ( P = 1.728 × 10 –6 ). None of these associations were observed in the HPV‐negative cohort, and this suggested their specificity to convey risk for HPV‐associated HNCs. In general, associations observed for HPV‐negative HNC were relatively weak, and variants in the HLA‐DPA1 region were the strongest among them ( P = 4.531 × 10 –4 ). Several lead signals reported by previous HNC genome‐wide association studies, including SNPs rs3135001 ( P = .012), rs1049055 ( P = .012), and rs34518860 ( P = .029) and allele HLA‐DQB1*06 ( P = .009), were replicated in the current study. However, these associations were limited to the HPV‐positive HNC group. Several cervical cancer–associated HLA variants, including SNPs rs9272143 ( P = .002) and rs9271858 ( P = .002) and alleles HLA‐B‐1501 ( P = .009) and HLA‐B‐15 ( P = .015), were also exclusively associated with HPV‐positive HNC. Conclusions: HPV‐positive HNC risk is associated with distinct HLA variants, and some of them are shared by both cervical cancer and HPV‐positive HNC. Human papillomavirus (HPV)–positive head and neck cancer (HNC) risk is associated with distinct human leukocyte antigen variants, and some of them are shared by both cervical cancer and HPV‐positive HNC. Lay Summary: Cervical cancer studies highlight that human papillomavirus (HPV)–driven cancer risk is linked with human leukocyte antigen (HLA) polymorphism. Hence, the current study was designed to investigate the HLA associations in HPV‐positive and HPV‐negative head and neck cancer (HNC) and compare these associations with cervical cancer. Several lead signals reported by previous HNC and cervical genome‐wide association studies were replicated in the current study. However, these associations were limited to the HPV‐positive HNC group, and this suggests that HPV‐positive HNC risk is associated with distinct HLA variants, and some of them are shared by both cervical cancer and HPV‐positive HNC.